PubChem 2019 update: improved access to chemical data. Issue Volume 47:Issue D1(2019) (29th October 2018) - Kim, Sunghwan; Chen, Jie; Cheng, Tiejun; Gindulyte, Asta; He, Jia; He, Siqian; Li, Qingliang; Shoemaker, Benjamin A; Thiessen, Paul A; Yu, Bo; Zaslavsky, Leonid; Zhang, Jian; et al.
Abstract: PubChem (https://pubchem.ncbi.nlm.nih.gov ) is a key chemical information resource for the biomedical research community. Substantial improvements were made in the past few years. New data content was added, including spectral information, scientific articles mentioning chemicals, and information for food and agricultural chemicals. PubChem released new web interfaces, such as PubChem Target View page, Sources page, Bioactivity dyad pages and Patent View page. PubChem also released a major update to PubChem Widgets and introduced a new programmatic access interface, called PUG-View. This paper describes these new developments in PubChem.